Top-down effects override climate forcing on reproductive success in a declining sea duck ... - Öst, Markus; Öst, Markus; Lehikoinen, Aleksi; Jaatinen, Kim (Dryad, 2021)
Population performance is predicted to be more strongly influenced by detrimental species interactions such as predation under benign climatic conditions, and by climate forcing under harsh conditions, reflected in geographical gradients in biotic interaction strength. Less appreciated is the potential for site-specific changes in drivers with the advent of anthropogenic alteration of predator-prey relationships, including apex predator restoration and spread of invasive predators. Particularly interesting is the relative impact of climate and biotic interactions on population performance when these conflict. In this 31-year study (1990-2020), we revisit a common eider (Somateria mollissima) population from SW Finland, Baltic Sea, fifteen years on from an earlier study showing that climate warming positively affected reproductive parameters and performance. However, the population is simultaneously exposed to increasing predation by the rapidly recovering native apex predator and invasive mammals. Based on ... : The 31-year data set covers 1990-2020, but there are some missing values. Thus, data on eider breeding parameters were unavailable from the breeding population of common eiders from Tvärminne in 1992, a final brood count at Tvärminne was not conducted in 1993, and migration data from the Hanko Bird Observatory was lacking from 1990. ...